2019
DOI: 10.2495/ei-v2-n3-272-282
|View full text |Cite
|
Sign up to set email alerts
|

Aspect of reproductive biology of Parachanna obscura, Gunther 1861 in a southwestern Nigerian reservoir

Abstract: African snakehead (Parachanna obscura) is a highly valued freshwater fish species in Nigeria, but its availability for economic and nutritional benefits is being threatened as a result of overdependence on wild source. Effort at bringing it to culture is, however, being limited by paucity of information on its biology among other challenges. Therefore, key aspects of the reproductive biology of this species were investigated as a prelude to artificially propagate it. 688 live samples comprise of 394 females (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…More fish was recorded in the dry season than in the wet season. This was in direct contrast with the findings of Kareem et al 11 (1:1.55) across the seasons, which showed an almost doubled female species over their male counterpart as with Olowo et al 12 and Ikpi and Okey 13 . This study however compared favorably with Akombo et al 18 and Taiwo and Odunaiya 19 where almost equal proportions of male and female numbers of these species were observed even though their abundance was in favour of female specimens.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…More fish was recorded in the dry season than in the wet season. This was in direct contrast with the findings of Kareem et al 11 (1:1.55) across the seasons, which showed an almost doubled female species over their male counterpart as with Olowo et al 12 and Ikpi and Okey 13 . This study however compared favorably with Akombo et al 18 and Taiwo and Odunaiya 19 where almost equal proportions of male and female numbers of these species were observed even though their abundance was in favour of female specimens.…”
Section: Discussioncontrasting
confidence: 71%
“…The sex of each sample was identified by visual examination and separated based on external morphology. The sex ratio was calculated according to Kareem et al 11 using the formula:…”
Section: Selection Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of first maturity of C. buettikoferi (♀ = 13 cm SL ; ♂ = 14.8 cm SL) and T. ansorgii (♀ = 6.9 cm LS ; ♂ = 8.1 cm LS) showed that most samples were from adult individuals, which indicates a low impact of fishing on fish size in the TESF. Although information on the length at first sexual maturity (Lm) of P. obscura is lacking in TESF, data from the literature (♀ = 25.8 cm LT ; ♂ = 26.6 cm LT) also indicated a heterogeneous population [37].…”
Section: Discussionmentioning
confidence: 99%